The Role of School Committees in Improving the Quality of Education (Study Case at SMK Negeri 2 Metro) - Makmun makmun (Syntax Idea)
This study aims to analyze and describe the role of school committees as considerations, support, controllers and mediators, in improving the quality of education at SMK Negeri 2 Metro. The research is carried out through a qualitative approach with a case study design. The research data was collected with in-depth interview techniques, observations, and documentation studies with informants as follows: School committees, principals, teachers, supervisors, parents of students of SMK Negeri 2 Metro. Data analysis is carried out by data reduction, data presentation, and drawing conclusions. To check the validity of the data is carried out with credibility, dependability, and confirmability. The results showed that the formation of the committee had referred to the provisions of laws and regulations and involved elements of the teacher council, the community, the government and the business and industrial world. The prominent role of the school committee is related to the provision of consideration and support, while the role of the committee as the controller is still limited in the use of the school budget and touches less on academic issues and evaluation of school performance. Likewise, the role of mediation is supported by stakeholders, considering that SMK collaborates with many elements. The school committee as an independent organization is very helpful in realizing quality education at SMK Negeri 2 Metro